STRUCTURE AND POWER FLEXIBILITY: SALES GADGET SPECIALIST (SGS) SMARTFREN TELECOM BANDUNG IN THE POST-MODERN ERA - Winda Ersa Putri; Dian Wardiana Sjuchro; S. Kunto Adi Wibowo; Isiaka Zubair Aliagan (Universitas Bunda Mulia, 2021)
Istilah